Synthesis of Cu Nanoparticles using Anredera cordifolia Extract and their Potential as Antidiabetic with Alpha Amylase Enzyme Inhibition - Munandar, Nurharis; Aritonang, Henry F.; Bonaventura, Ridho; Wijaya, Dwi Putra (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2025)
This study reports a green synthesis of copper nanoparticle using binahong (Anredera cordifolia) leaf extract as both a bioreductant and a capping agent. The synthesis was optimized by varying the extract-to-precursor ratio (1:3, v/v) and the reaction pH (6–11) with pH 10 selected as the optimal condition for nanoparticle preparation. Nanoparticle formation was confirmed using UV–Vis spectroscopy, showing a strong absorption band at 325 nm, indicative of oxide-based copper nanostructures and/or surface oxidation during green synthesis. XRD patterns revealed Cu2O as the dominant crystalline phase, characterized by reflections at 2θ ≈ 29.6°, 36.4°, 42.3°, 61.3°, 73.5°, and 77.3°, with a possible minor contribution from metallic Cu due to peak overlap. FTIR spectra confirmed the presence of biomolecules (O–H and C–H bands, along with carbonyl/COO−-related bands) involved in nanoparticle stabilization, as well as Cu–O vibrations around 600–620 cm−1 consistent with Cu2O. PSA showed a dominant hydrodynamic size in the 60–70 nm range (average 65 nm), whereas SEM indicated aggregation into micrometer-scale clusters upon drying. In vitro α-amylase inhibition assays demonstrated concentration-dependent inhibition, with CuNPs (IC50 6.18 μg/mL) and the extract + CuNPs mixture (IC50 6.83 μg/mL) approaching that of acarbose (IC50 5.04 μg/mL) and exhibiting stronger activity than the extract alone (IC50 8.89 μg/mL). The key contribution of this work is the development of a simple, aqueous, environmentally friendly route that leverages local biological resources while producing Cu2O-rich nanoparticles with α-amylase inhibitory activity approaching that of acarbose. These findings highlight the promise of a low-cost antidiabetic candidate for postprandial glucose control and provide a basis for further investigations into nanoformulation and preclinical evaluation.